Model Aplikasi Pengelolaan Administrasi Lembaga Sertifikasi Profesi di Perguruan Tinggi - Kirana, Eka Chandra; Ruslan, M.; Khairullah, Khairullah; Martono, Prio Setyo (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
Administrative management at Professional Certification Institutions (LSP) is very important because LSPs must comply with various standards and regulations set by accreditation bodies and the government. Good administrative management ensures that all documents, processes and procedures comply with requirements, and ensures that this data is stored and managed safely, and can be accessed easily when needed. The STMIK Banjarbaru Professional Certification Institute (LSP) is an institution established to carry out competency assessments and competency certification for STMIK Banjarbaru students. At LSP STMIK Banjarbaru, the process begins when the assessee obtains information about the certification scheme offered by LSP, requirements, costs and registration procedures. This information is obtained from officers in the LSP STMIK Banjarbaru section. After completing the required documents, the assessment is carried out according to a predetermined schedule. The results of the competency test will be announced via WhatsApp media groups. Implementing the STMIK Banjarbaru Professional Certification Institute (LSP) Administration Management Application can provide convenience and increase the operational efficiency and effectiveness of the Professional Certification Institute (LSP). By automating various administrative processes, from participant registration to reporting certification results, we can reduce administrative errors and speed up processing time.Keywords: Certification; Professional Certification Institute; AdministrationÂ AbstrakPengelolaan administrasi pada Lembaga Sertifikasi Profesi (LSP) sangat penting karena LSP harus mematuhi berbagai standar dan regulasi yang ditetapkan oleh badan akreditasi dan pemerintah. Pengelolaan administrasi yang baik memastikan bahwa semua dokumen, proses dan prosedur sesuai dengan persyaratan, serta memastikan bahwa data ini disimpan dan dikelola dengan aman, serta dapat diakses dengan mudah saat dibutuhkan. Â Lembaga Sertifikasi Profesi (LSP) STMIK Banjarbaru adalah lembaga yang didirikan untuk pelaksanaan asesmen kompetensi dan sertifikasi kompetensi bagi mahasiswa STMIK Banjarbaru. Pada LSP STMIK Banjarbaru, proses dimulai ketika asesi memperoleh informasi tentang skema sertifikasi yang ditawarkan oleh LSP, persyaratan, biaya, dan prosedur pendaftaran.Informasi tersebut didapatkan dari petugas pada bagian LSP STMIK Banjarbaru. Setelah melengkapi berkas persyaratan, asesmen dilaksanakan sesuai jadwal yang sudah ditentukan. Hasil dari uji kompetensi akan diumumkan melalui media groups whatapps. Penerapan Aplikasi Pengelolaan Administrasi Lembaga Sertifikasi Profesi (LSP) STMIK Banjarbaru dapat memberikan kemudahan serta meningkatkan efisiensi dan efektivitas operasional Lembaga Sertifikasi Profesi (LSP). Dengan mengotomatisasi berbagai proses administrasi, mulai dari pendaftaran peserta hingga pelaporan hasil sertifikasi, mampu mengurangi kesalahan administratif dan mempercepat waktu pemrosesan.Â